PENGARUH STRUKTUR MODAL, PROFITABILITAS DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Murfiqoh, Apriliani; Sri Handayani (Jurnal Ilmu Akuntansi, 2024)
The main concern of investors when deciding how to invest in a company is the value of the company. Companies with a higher value are more attractive to investors. This study examines the impact of capital structure, profitability and good corporate governance on firm value. This study uses a causal design with multiple linear regression analysis. The sampling method used is the saturated sampling method, with a population consisting of non-financial sector BUMN entities on the Indonesia Stock Exchange during the period 2019-2022 with a total of 80 data and a sample of 80 data.  The secondary data were obtained from the financial reports published on the official website of the Indonesian Stock Exchange during the period considered. The results show that capital structure, profitability and GCG simultaneously affect firm value. Furthermore, GCG has a negative effect on firm value. Then, there is no effect of capital structure on firm value and profitability has no effect on firm value. The results of this study support the theory of the relevance of accounting information, where good corporate governance is bad news for investors and requires high costs.